Hemodynamic Predictors of Renal Function After Pediatric Left Ventricular Assist Device Implantation. Issue 12 (10th May 2021) - Chen, Chiu-Yu; Montez-Rath, Maria E.; May, Lindsay J.; Maeda, Katsuhide; Hollander, Seth A.; Rosenthal, David N.; Krawczeski, Catherine D.; Sutherland, Scott M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Although renal function often improves after pediatric left ventricular assist device (LVAD) implantation, recovery is inconsistent. We aimed to identify hemodynamic parameters associated with improved renal function after pediatric LVAD placement. A single-center retrospective cohort study was conducted in patients less than 21 years who underwent LVAD placement between June 2004 and December 2015. The relationship between hemodynamic parameters and estimated glomerular filtration rate (eGFR) was assessed using univariate and multivariate modeling. Among 54 patients, higher preoperative central venous pressure (CVP) was associated with eGFR improvement after implantation ( p = 0.012). However, 48 hours postimplantation, an increase in CVP from baseline was associated with eGFR decline over time ( p = 0.01). In subgroup analysis, these associations were significant only for those with normal pre-ventricular assist device renal function ( p = 0.026). In patients with preexisting renal dysfunction, higher absolute CVP values 48 and 72 hours after implantation predicted better renal outcome ( p = 0.005). Our results illustrate a complex relationship between ventricular function, volume status, and renal function. Additionally, they highlight the challenge of using CVP to guide management of renal dysfunction in pediatric heart failure. Better methods for evaluating right heart function and volume status are needed to improve our understanding of how hemodynamics impact renal function in this population.